(NpROBLEMY FIZIKI SOLNE^NYH WSPY[EK (B:s (NtRUDY (BIV (NEVEGODNEGO SEMINARA(B, (NlENINGRAD (B[(NpULKOWO(B, 28-31] (NOKTQBRX (B1985 (NG(B. /s - (NiWANOW(B-(NhOLODNYJ(B, (NgOR sEMENOWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B. (NW KONCE DOKL(B.s
(NrEZ(B. (NDOKL(B.: (NANGL(B.s
(Nw NADZAG(B.: (Nan sssr(B, (NiN(B-(NT ZEMNOGO MAGNETIZMA(B, (NIONOSFERY I RASPROSTRANENIQ RADIOWOLNs
Keywords: (NsOLNE^NYE WSPY[KIs; (NfIZIKAs